Analysis Of Face Milling Performance On Inconel 718 Using FEM And Historical Data Of RSM - Chan, Chee Hoong; Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Abu Bakar, Hamizan; Sundi, Syahrul Azwan; Zakaria, Kamarul Ariffin; Che Haron, Che Hassan; Abdul Ghani, Jaharah; Mohd Shahrim, Mohammad Shah All Hafiz (IOP Publishing Ltd., 2017)
This study involves conducting finite element (FE) analysis on face milling of Inconel 718 and investigating the effect of cutting parameters to resultant force and tool temperature. The cutting parameters considered include cutting speed in the range of 20 to 40 m/min, feed rate in the range of 0.10 to 0.20 mm/tooth and depth of cut in the range of 0.1 to 0.2 mm. The experimental approach is carried out using Analysis of Variance (ANOVA) and Response Surface Methodology (RSM). According to the results, the significant factors that affect the resultant force are feed rate and depth of cut. On the other hand, cutting speed has no significant impact on the resultant force. The interaction between feed rate and depth of cut has the most influence on the resultant force. Meanwhile, all cutting parameters considered significantly affect the tool temperature. Through the RSM method, the obtained optimal setting of the parameters is 23.13 m/min, 0.10 mm/tooth and 0.10 mm for cutting speed, feed rate and depth of cut, respectively. The simulated results are then validated by an experiment. It is found that the percentage of relative error between the FE simulation and the actual experiment for resultant force and tool temperature is 10% and 31%, respectively. Considering all possible errors, the overall trend of the simulated results is reasonably in a good agreement with the experimental results.